Comparative experiment on the efficiency of water cooling in photovoltaic modules in the climatic conditions of Southern Russia - Ilyichev, V. G.; Zaynutdinova, L. Kh; Terukov, E. I.; Mikhailov, M. Yu (Глобальная ядерная безопасность, 2023)
The problems of ensuring the safety of operation of nuclear power plants are always paid increased attention. In addition to the self-contained diesel generator sets used to maintain the operation of safety systems in case of loss of external power supply, it is also advisable to consider the use of more environmentally friendly self-contained photovoltaic units at this stage. The work is aimed at a comparative experimental study of the efficiency of water cooling in real natural climatic conditions of Southern Russia. In this experiment, cooled and uncooled photovoltaic modules are simultaneously exposed to a complex of variable weather factors: solar radiation, cloudiness, wind, pressure, temperature and humidity of the environment. Both modules have loads connected via MPPT controllers. The effect of water cooling on the energy efficiency of photovoltaic modules assembled from silicon heterojunction technology (HJT) solar cells was studied. The solar panels were made from 130 micron thick HJT cells interconnected using SmartWire contact technology. It reduces power loss due to possible defects such as cracks. The conditions for ensuring the highest degree of similarity between the parameters of the cooled and uncooled modules have been met. A comparative experimental study was conducted in Astrakhan State University using a long-term monitoring system for the characteristics of photovoltaic modules. This is a test photovoltaic system (TPS), built on the basis of the Paragraph PL2 electronic recorder. A significant increase in module output when working with cooling was established. At insolation of 987.5 W/m2, the power generated by the cooled module was 93.0297 W, while the power of the module without cooling was 79.306 W. The difference comprised 13.7237 watts. Power increased by 17%. In the experiment, the average efficiency value when the module was cooled was 0.15977. When uncooled, it was 0.13764. The efficiency intensified by 2.21%. This increase is significant. The results obtained confirm the fairly high efficiency of water cooling in photovoltaic modules in real natural operating conditions for regions with high ambient temperatures, Southern Russia, in particular